Dark day in the deep sea - Osborne, Mary Pope.; Murdocca, Sal (New York : Random House, 2008)
When eight-year-old Jack and his seven-year-old sister, Annie, join a group of nineteenth-century explorers aboard the H.M.S. Challenger, they learn about the ocean, solve the mystery of its fabled sea monster, and gain compassion for their fellow creatures.
"A Merlin mission."
"A Stepping Stone book."
520
Keywords: Challenger (Ship : 1872-1876) -- Juvenile fiction; Oceanography -- Juvenile fiction; Compassion -- Juvenile fiction; Time travel -- Juvenile fiction; Magic -- Juvenile fiction; Tree houses -- Juvenile fiction; Brothers and sisters -- Juvenile fiction; Fantasty fiction